In vivo retinal imaging is associated with cognitive decline, blood-brain barrier disruption and neuroinflammation in type 2 diabetic mice - Majimbi, May; McLenachan, Samuel; Nesbit, Michael; Chen, Fred K.; Lam, Virginie; Mamo, John; Takechi, Ryu (Frontiers in Endocrinology, 2023)
Type 2 diabetes (T2D) is associated with chronic inflammation and neurovascular changes that lead to functional impairment and atrophy in neural-derived tissue. A reduction in retinal thickness is an early indicator of diabetic retinopathy (DR), with progressive loss of neuroglia corresponding to DR severity. The brain undergoes similar pathophysiological events as the retina, which contribute to T2D-related cognitive decline.This study explored the relationship between retinal thinning and cognitive decline in the LepR db/db model of T2D. Diabetic db/db and non-diabetic db/+ mice aged 14 and 28 weeks underwent cognitive testing in short and long-term memory domains and in vivo retinal imaging using optical coherence tomography (OCT), followed by plasma metabolic measures and ex vivo quantification of neuroinflammation, oxidative stress and microvascular leakage.At 28 weeks, mice exhibited retinal thinning in the ganglion cell complex and inner nuclear layer, concomitant with diabetic insulin resistance, memory deficits, increased expression of inflammation markers and cerebrovascular leakage. Interestingly, alterations in retinal thickness at both experimental timepoints were correlated with cognitive decline and elevated immune response in the brain and retina. These results suggest that changes in retinal thickness quantified with in vivo OCT imaging may be an indicator of diabetic cognitive dysfunction and neuroinflammation.